The perception of opportunities and threats in Polish companies within the context of outsourcing use – research results - Drzewiecki, Jakub (Wybrane aspekty zarządzania procesami, projektami i ryzykiem w przedsiębiorstwach, 2020)
The purpose of the paper is to identify and analyse the impact of perceptions of opportunities and threats on the scope and maturity of outsourcing used in Polish enterprises. The article presents the results of quantitative research conducted on a sample of 281 Polish enterprises. The research results indicate at most a weak level of correlation between the perception of opportunities and threats and the scope of the outsourcing used. The study confirmed the impact of perception of opportunities and threats on outsourcing maturity, with this impact being slightly stronger for opportunities than threats. Among the four dimensions of outsourcing maturity identified, the perception of opportunities and threats had the greatest impact on the analytical activities accompanying its implementation.